Thermo-Catalytic Methane Decomposition for Hydrogen Production: Effect of Palladium Promoter on Ni-based Catalysts - Irene Lock Sow Mei; S.S.M. Lock; Dai-Viet N. Vo; Bawadi Abdullah (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2016)
Hydrogen production from the direct thermo-catalytic decomposition of methane is a promising alternative for clean fuel production. However, thermal decomposition of methane can hardly be of any practical and empirical interest in the industry unless highly efficient and effective catalysts, in terms of both catalytic activity and operational lifetime have been developed. In this study, the effect of palladium (Pd) as a promoter onto Ni supported on alumina catalyst has been investigated by using co-precipitation technique. The introduction of Pd promotes better catalytic activity, operational lifetime and thermal stability of the catalyst. As expected, highest methane conversion was achieved at reaction temperature of 800 °C while the bimetallic catalyst (1 wt.% Ni -1wt.% Pd/Al2O3) gave the highest methane conversion of 70% over 15 min of time-on-stream (TOS). Interestingly, the introduction of Pd as promoter onto Ni-based catalyst also has a positive effect on the operational lifetime and thermal stability of the catalyst as the methane conversion has improved significantly over 240 min of TOS.